A 5 × 200 Gbps microring modulator silicon chip empowered by two-segment Z-shape junctions - Yuan, Yuan; Peng, Yiwei; Sorin, Wayne V.; Cheung, Stanley; Huang, Zhihong; Liang, Di; Fiorentino, Marco; Beausoleil, Raymond G. (Nature communications, 2024)
Optical interconnects have been recognized as the most promising solution to accelerate data transmission in the artificial intelligence era. Benefiting from their cost-effectiveness, compact dimensions, and wavelength multiplexing capability, silicon microring resonator modulators emerge as a compelling and scalable means for optical modulation. However, the inherent trade-off between bandwidth and modulation efficiency hinders the device performance. Here we demonstrate a dense wavelength division multiplexing microring modulator array on a silicon chip with a full data rate of 1 Tb/s. By harnessing the two individual p-n junctions with an optimized Z-shape doping profile, the inherent trade-off of silicon depletion-mode modulators is greatly mitigated, allowing for higher-speed modulation with energy consumption of sub-ten fJ/bit. This state-of-the-art demonstration shows that all-silicon modulators can practically enable future 200 Gb/s/lane optical interconnects. The authors showcase a five-channel silicon microring modulator array with a total data rate in the terabit range. Each microring is equipped with two separate Z-shape junctions to overcome the bandwidth and modulation efficiency trade-off, providing a pathway for future 200 Gb/s/lane silicon optical interconnects.